Menilai kesadaran keberlanjutan Mahasiswa; bukti empiris melalui Analisis Rasch - Khairati, Ikmanisa; Lufri, Lufri; Festiyed, Festiyed; Usmeldi, Usmeldi; Mawardi, Mawardi (Biosfer: Jurnal Pendidikan Biologi, 2025)
Sustainability consciousness acts as a compass in making considerations, behaving, and acting with attention to sustainability aspects. This research aims to determine how the sustainability consciousness of high school students is assessed using the Sustainability Consciousness Questionnaire (SCQ), which has been adapted and tailored to the research context. The collected data were analyzed using comprehensive Rasch modeling to measure latent variables. The Rasch analysis was conducted using the Winsteps application, focusing on validity, reliability, student sustainability consciousness, and Differential Item Functioning (DIF). Based on the Rasch analysis, it was found that the sustainability consciousness of the students was relatively good and varied across three analyzed dimensions: sustainability knowingness, sustainability attitudes, and sustainability behavior. The DIF analysis revealed that there were two items out of a total of 27 that fell into the DIF category. This indicates that there are differences in responses shown by male and female students. These findings support previous research regarding how attitudes toward sustainability differ based on gender. Furthermore, the topics explored in biology learning are highly relevant to the majority of issues that are central to sustainability concerns. Therefore, through biology education, students’ knowledge, attitudes, and behaviors can be nurtured and developed. In this way, the knowledge they acquire can be transformed into concrete actions. Moreover, this study contributes to empirical research on sustainability consciousness demonstrated by high school students.